2016
DOI: 10.1111/jen.12302
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effect of beta‐cypermethrin on development and fertility of the Asian multicoloured ladybird beetle Harmonia axyridis

Abstract: The Asian multicoloured ladybird beetle, Harmonia axyridis, is utilized as a major natural enemy of aphids in the field, greenhouses and orchards. However, it has been looked as invasive predator distributing in worldwide. To refine integrated pest management (IPM) against aphids, it is important to evaluate the effects of insecticides on physiology and behaviour of the high adapted predators. Beta‐cypermethrin, a broad‐spectrum insecticide, not only kills aphids at lethal concentrations but also affects natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…However, sublethal concentrations of insecticides may also induce positive effects on insect bionomics2627. Sublethal concentrations of beta-cypermethrin lead to increased fecundity of Harmonia axyridis 30. When treated with sublethal concentrations of avermectin as immatures, Panonychus citri have shorter generation doubling times and greater intrinsic growth rates than untreated immatures28.…”
Section: Discussionmentioning
confidence: 99%
“…However, sublethal concentrations of insecticides may also induce positive effects on insect bionomics2627. Sublethal concentrations of beta-cypermethrin lead to increased fecundity of Harmonia axyridis 30. When treated with sublethal concentrations of avermectin as immatures, Panonychus citri have shorter generation doubling times and greater intrinsic growth rates than untreated immatures28.…”
Section: Discussionmentioning
confidence: 99%
“…The LC 5 of beta-cypermethrin for H. axyridis was 3.158 mg L −1 as it was estimated in a sister study by Xiao et al ( 2016 ). The ladybirds were exposed to the insecticide using the method of exposure to pesticide residues in glass tubes (see Desneux et al, 2004a , b , c ).…”
Section: Methodsmentioning
confidence: 61%
“…Numerous studies have reported that sublethal doses of pesticides may impact arthropods (Liang et al, 2012 ; He et al, 2013 ; Pan et al, 2014 ; Chen et al, 2015 ; Fekri et al, 2016 ; Guedes et al, 2016 ) and notably natural enemies such as coccinellids (Desneux et al, 2007 ). Studies showed that various aspects of the biology of coccinellids may be altered by pesticides, including development (Yu et al, 2014 ), prey consumption (Wang and Shen, 2002 ; Singh et al, 2004 ; He et al, 2012 ), reproduction (Galvan et al, 2005 ; Rahmani and Bandani, 2013 ; Xiao et al, 2016 ), and metabolic mechanisms related to detoxification (Zhang et al, 2012 ; Tang et al, 2014 ). Evaluating the side-effects of sublethal doses of pesticides may help depicting possible adaptations of predatory insects to sublethal toxic pressures; it may also provide more information to improve the application of biological control agents in combination with sprayed pesticides in agricultural IPM systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMX applied systemically did not adversely affect the functional response of H. axyridis; therefore, systemic application of TMX (e.g., stem application) might be available to minimize potential negative effects on natural enemies in Chinese cabbage fields. Moreover, a reduction in the consumption capacity of H. axyridis may affect its reproductive capacity, which would inhibit population growth and consequently affect performance in pest management programs (Stark & Banks, 2003;Desneux et al, 2007;Xiao et al, 2016b). Therefore, further, longer term studies are required to fully investigate the possible effects on the development and fecundity of H. axyridis after exposure to TMX and/or consuming TMX-contaminated prey.…”
Section: Resultsmentioning
confidence: 99%